Correction to: Timely initiation of breastfeeding in Zimbabwe: evidence from the demographic and health surveys 1994–2015 - Sanni Yaya; Ghose Bishwajit; Gebretsadik Shibre; Amos Buh (International Breastfeeding Journal, 2020)
Following publication of the original article [1], the authors have flagged that the article contains the following errors: